PENGARUH PELATIHAN DETEKSI DINI PERKEMBANGAN MENTAL EMOSIONAL ANAK TERHADAP PENGETAHUAN, MOTIVASI DAN KETERAMPILAN KADER POSYANDU DI WILAYAH PUSKESMAS SEWON II, BANTUL - , CHANDRA LIA KUSUMAWARDANI; , Sri Hartini S.Kep., Ns., M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Preschool children are children in golden period of development especially in mental emotional development. Early detection of mental emotional development is needed so as to be able to identify disorder and make necessary intervention since child development will influence the next phase of development. Early detection can be carried out by posyandu cadres who have got knowledge and skills on early detection from early detection training on child mental emotional development. Objective:To identify effect of early detection training on child mental emotional development for posyandu cadres at the area of Sewon II Health Center, Bantul. Method:The study was a pre experimental one group pretest posttest implemented to 39 posyandu cadres. Research instruments used questionnaire of knowledge on early detection of child mental emotional development to assess knowledge, questionnaire of motivation to assess motivation and checklist of skills to assess skills of the cadres. Result: Knowledge of posyandu cadres before training was mainly low in 32 cadres (82%). Knowledge after training was average in 17 cadres (43.7%). As many as 22 cadres (56.4%) had average level of motivation and the majority (28 cadres or 71.8%) had average level of skills. There was increase of knowledge of posyandu cadres before and after training with average deviation ±SD 3.7 ± 2.93. Conclusion: There was increase of knowledge in posyandu cadres before and after training with average deviation ±SD 3.7 ± 2.93.